KORELASI ANTARA PERILAKU BERKELOMPOK DAN HASIL PRESENTASI PETA KONSEP SISWA DALAM PEMBELAJARAN KOOPERATIF BERBASIS MODUL ETNOSAINS SUBAK - Thalia Prasetya; Dewa Ayu Puspawati (Jurnal Santiaji Pendidikan (JSP), 2013)
Based on the observation that the information obtained in the junior Amarawati Tampaksiring is one of the schools that implement conventional learning models. To achieve the goal of education, conventional learning model is not very effective to implement. Therefore, innovation is required in learning. One way to do is to implement a module based cooperative learning etnoscience subak which emphasizes the aspects of group behavior and results presentation concept maps. The purpose of this study was to determine the effect of cooperative learning modules based on behavior etnoscience subak groups and the results of students' concept map presentation, as well as to determine the correlation between the behavior of the group and the results presentation concept maps. The experiment was conducted in the junior class VII B Amarawati Tampaksiring. Students were divided into six groups, and each group working on a concept map. Furthermore, observers provide an assessment with reference to the assessment rubric. From the data analysis, the results obtained flocking behavior scores increased from 273.5 to 497.5 with a significance level (p = 0.028 <0.05), which means learning a given effect on the behavior of groups of students. Increase also occurred in the results presentation concept maps where scores increased from 42.0 to 97.0 with a significance level (p = 0.027 <0.05), which shows the influence of learning the presentation of the results of students' concept maps. To test the correlation between the behavior of the group with the results presentation concept maps, correlation coefficient (ρ = 0.986) indicating increasing students flocking behavior, the result presentation concept maps is increasing as well. Results significance level (p = 0.000 <0.05) showed that the flocking behavior correlates to the presentation of the results of students' concept maps. In conclusion, cooperative learning modules based etnoscience subak affect the increase in groups as well as the behavioral aspects of students' concept map presentation of results, and the two variables have a positive correlation in the study.